Pteridophyta in the Puncak Gaduang Area, Lubuk Basung, Agam Regency as a Learning Media for Plantae Materials - Suci Mahesa; Siska Nerita; Abizar Abizar (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
Ferns (Pteridophyta) are plants that can live easily in various habitats, both epiphytic, terrestrial and aquatic. The Puncak Gaduang Lubuk Basung area of Agam Regency is generally located in a lowland area, with the condition of the land having changed from hills to plantations and a place for taking soil for making bricks, but many types of ferns grow and develop in this area. The purpose of this study was to determine the types of ferns found in the Puncak Gaduang area, Lubuk Basung, Agam Regency and produce a valid herbarium. The method used in this study is a survey method with field observations first in taking ferns. The sampling technique is exploration, and the 4D model is used for the herbarium. The results of the study found 24 species of ferns consisting of 10 families, 4 orders and 2 classes. The validity test on the herbarium is included in the valid category. It can be concluded that and the learning media in the form of a herbarium was suitable for use as a learning medium in schools.